Sea Fence and Public Policy: Impact on the Welfare of Fishermen Families in Tangerang, Indonesia - Harry, Musleh; Fakhrudin, Fakhrudin; Wahidi, Ahmad; Jannani, Nur; Fajari, Meisy (El-Usrah: Jurnal Hukum Keluarga, 2025)
Indonesia, as an archipelagic country, possesses a vast geographical area and an extensive coastline. Its coastal areas hold abundant natural resource potential, such as tourism assets, fisheries, seaweed, and coral reefs, all of which offer economic value and contribute to the welfare of local communities. This study employed an empirical juridical method and analyzed the issues of sea fence and public policy on the welfare of fishermen families in Tangerang, Indonesia, through the lens of public policy theory. Data were collected by means of interviews, document analysis, and a review of laws and regulations. Findings reveal that a lack of environmental impact assessments, community involvement, and transparency have rendered the sea fence construction policy ineffective. Additionally, sea fences have a direct impact on the well-being of fishing families, including reduced incomes, health problems, restricted access to fishing areas, higher operating expenses, and detrimental effects on marine biodiversity and seawater quality. Hence, efforts must be made to address the issues surrounding sea fences to enhance the welfare of fishermen and their families. Government policies on sea fences should include increasing the capacity of fisherman’s families through training and education, establishing supporting infrastructure, and boosting fishermen and local community organizations. Policy review, more dialogic communication, and the implementation of fairer and more sustainable fisheries welfare measures are among the recommendations.